Evaluasi Dimensi & Kepatuhan Clinical Pathway Apendisitis Akut di RS PKU Muhammadiyah Yogyakarta - Elsye Maria Rosa; Aviv Aziz Triono (Jurnal Admmirasi, 2017)
Incidence of acute appendicitis in Indonesia is quite high, after dyspepsia, gastritis, duodenitis and other digestive system diseases. Incidence of acute appendicitis is found with different conditions, integrated pathways are used to reduce disease variation, cost efficiency, service according to standard procedures and evidence based medicine. The objective of the study was to evaluate the accuracy and to assess the adherence of integrated pathway of acute appendicitis in PKU Muhammdiyah Hospital of Yogyakarta. This research used case study method with descriptive quantitative statistic design, number of sample from November 2015 until end of January 2016 (n = 38). To evaluate the accuracy of using the Integrated Care Pathway Appraisal Tool (ICPAT) which consists of six dimensions and to assess compliance by comparing the services provided to patients with integrated pathway sheets. Evaluation of the dimensions of acute appendicitis pathway: Dimension 1 (true integrated pathway) content 70% (moderate) and quality 100% (Good), dimension 2 (documentation) content 48% (less) and quality 25% (less), dimension 3 content 54% (less) and 65% quality (moderate), dimension 4 (application) content 60% (moderate) and quality 100% (good), dimensions 5 (maintenance) content 50% (moderate) and quality 31 % (less), dimension 6 (role of organization) content 67% (moderate) and quality 55% (moderate). Adherence level: Admission process obedient 100%, diagnosis & pre-therapy obedient 100%, and therapy with 29% compliance. Conclusions: It is necessary to evaluate the accuracy of the pathway of acute appendicitis dimension and its application at least once a year. The integrated team tasked with correcting the implementation (the completeness of the medical record and integrated pathway documents, the compliance by the specialists and the results reported as the evaluation material..